Analysing Trade Creation and Trade Diversion effects in ECOWAS Regional Trade Agreement - Oladimeji Fajimolu; Olabode Olayemi (Universitas Trisakti, 2023)
Aim/Purpose – The study focuses on trade creation and trade diversion effect in the Economic Community of West African States (ECOWAS) regional trade agreement. It examines if the ECOWAS regional trade agreement has brought about trade creation and/or trade diversion before the period of ban on certain items of importation by the Nigerian government as against the terms of the agreement. Methodology – The study uses augmented gravity model. Estimations were carried out on bilateral trade flows, trade creation and trade diversion within the region. Secondary data (2008-2018) were obtained from reliable sources. Ordinary least squares (OLS) and panel data regression was used to analyze the data. Findings – It was found that the GDP (wealth), population and political stability of the exporting countries will significantly foster intra-regional bilateral trade flow while variables like land area, landlocked and distance will significantly reduce bilateral trade flow in the region. The population, landlocked, political stability and corruption perception variables of the importing countries are found not to be statistically significant. R2 being the coefficient of determination falls between 54.8% and 63.3% which implies that the independent variables have been able to explain 54.8% to 63.3% of the total variations in the dependent variable. Research implications – Membership of some of the ECOWAS members in Global System of Trade Preferences among developing countries (GSTP) was found to have resulted in trade diversion; whereas, participation of some of ECOWAS members in West African Economic and Monetary Union (WAEMU) has contributed to the level of trade creation in ECOWAS region. Originality/value/contribution – The level of trade creation in the ECOWAS region can be improved upon provided all member states adhere strictly to the terms of the agreement.